Long Term Impact of Exchange Rate Fluctuations (US Dollar vs. Euro) on OPEC Oil Prices - Gahraman Abdoli; Michael Vellaei yamchi (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2011)
When the exchange rate of the dollar fluctuates, a  disequilibrium is created in the market for crude oil. This will be reflected in altered Demand for crude oil and an altered oil price and oil revenue. A depreciation of the dollar may lead to an increase in Demand for crude oil in other currency zones (Euro, Yuan, zudian Rupie, etc). In this paper we investigate the Long-term relationship between oil price and oil exchange rates oil Import china and India by using a nominal monthly from2006:1 to 2010:12.The results show that nominal depreciation is us Dollar vs. Euro and Chinese Yuan has a significantly positive effect on OPEC oil prices. Whereas the change of Dollar value va. Indian Rupie has no significant effect on oil prices.